146 Diagnostic test use by children in Oxfordshire from 2005 to 2020: a retrospective cohort analysis. (8th June 2022) - Thomas, Elizabeth; Shine, Brian; Gill, Peter; Heneghan, Carl; Perera, Rafael
Abstract : Background: Substantial variation has been demonstrated in the use of diagnostic tests across primary and secondary care. Most of this research focuses on tests requested for adults and there is a paucity of comprehensive data that quantifies and analyses diagnostic test use in children. It is unknown what proportion of tests occur in primary care compared with secondary care (inpatient or outpatient). Objectives: To quantify the most frequently performed laboratory tests for children in the Oxfordshire region (Oxford University Hospitals and Oxfordshire General Practices) To assess how laboratory test use has changed from 2005 to 2020 To determine the proportion of laboratory tests that are performed in primary care compared with secondary care. Methods: This was a retrospective analysis of laboratory test data from the clinical laboratories at the Oxford University Hospitals Trust, including primary and secondary care data from 1st January 2005 to 31st December 2020. Children under the age of 16 who received a diagnostic test during the study period were included in the analysis. The annual rates of test use were adjusted by the population of children aged 0 to 15 in Oxfordshire from 2005 - 2020. The proportion of tests requested in primary care compared to secondary inpatient and outpatient care were also calculated. Results: A total of 11, 044, 960 individual laboratory tests were performed in 124, 066 children (66, 924 males and 57, 142 females) aged between 0 - 15 years from 2005 to 2020. Preliminary analyses of individual test components (e.g., haemoglobin) demonstrated an increase in adjusted testing utilisation rates since 2005. The most frequently performed laboratory test panels overall were (1) Full blood count (FBC); (2) Urea and electrolytes; (3) Liver function tests; (4) Blood gas; and (5) FBC differential respectively. 75% of tests were performed in the inpatient setting (n = 8, 249, 889 of 11, 044, 960 tests) and 11% of tests were performed in the outpatient setting (n = 1, 199, 685 of 11, 044, 960 tests). 14% of laboratory tests were performed in primary care (n = 1, 595, 376 of 11, 044, 960 tests). Test utilisation rates for test panels (including FBC, Urea and electrolytes), and subgroup analyses of test utilisation rates for developmental age groups, sex and setting will be presented. Conclusions: Tests that demonstrate large increases in utilisation over time may represent over-testing. Identifying the setting in which certain tests with high variation in use are more commonly performed can highlight where interventions such as improved testing guidance for clinicians can be implemented. The findings of this study will inform further research analysing and quantifying geographic and temporal variation for the most frequently performed tests in English primary care.